Perspectives of students belonging to CAU Neiva, about their learning process of English in distance education (2018)
Neiva is a Colombian municipality, capital of the department of Huila. This city is born between the Cordillera Central and Eastern, on a plain on the east bank of the Magdalena River in the valley of the same name, crossed by the Ceibas river and the river del Oro. Its land area of 1533 square kilometers, its height 442 meters above sea level and an average temperature of 27.7 ° C.4. This research was developed in the Santo Tomas university at campus of Neiva (CAU Neiva). which was created in the year 1987, offering its 37 municipalities the modality of Distance Education with the Faculties of Education and Sciences and technologies, that campus is located in the address Avenida La Toma 7 - 60, this has two classroom and hallway which are used by students and teachers each weekend in the tutorials provided by Santo Tomas university. This campus also has women's bathroom and a men's bathroom, one library, one system room and the office of principal and secretary of this campus; in this campus is offered The B.A. in foreign language- English, this program is composed by 20 students including two graduating students, 12 of 20 students were interviewed and surveyed, with this information was development this study; some of these students are full- time and part- time workers; students of English program in Neiva have different occupations, for example some of them are teachers (preschool and primary teachers), professional soldiers, secretaries, receptionist, students, sellers etc.